2009
DOI: 10.1088/0004-637x/702/1/680
|View full text |Cite
|
Sign up to set email alerts
|

ON MAGNESIUM SULFIDE AS THE CARRIER OF THE 30 μm EMISSION FEATURE IN EVOLVED STARS

Abstract: A large number of carbon-rich evolved objects (asymptotic giant branch stars, protoplanetary nebulae, and planetary nebulae) in both the Milky Way galaxy and the Magellanic Clouds exhibit an enigmatic broad emission feature at ∼ 30 µm. This feature, extending from ∼ 24 µm to ∼ 45 µm, is very strong and accounts for up to ∼ 30% of the total infrared luminosity of the object. In literature it is tentatively attributed to magnesium sulfide (MgS) dust. Using the prototypical protoplanetary nebula around HD 56126 f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 23 publications
1
46
1
Order By: Relevance
“…Another explanation is that MgS is not the carrier of the 30 μm band. A critical assessment of all previous MgS studies was made by Zhang et al (2009) who pointed out that the mass of MgS derived from the emission at 30 μm violated the available abundances of Mg and S in the stellar atmospheres, owing to the use of improper optical constants for MgS in the optical and UV wavelength domains. Alternative solids have been proposed (e.g., hydrogenated amorphous carbon, HAC, Grishko et al 2001).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Another explanation is that MgS is not the carrier of the 30 μm band. A critical assessment of all previous MgS studies was made by Zhang et al (2009) who pointed out that the mass of MgS derived from the emission at 30 μm violated the available abundances of Mg and S in the stellar atmospheres, owing to the use of improper optical constants for MgS in the optical and UV wavelength domains. Alternative solids have been proposed (e.g., hydrogenated amorphous carbon, HAC, Grishko et al 2001).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Neither S nor Zn shows much affinity for dust, although MgS has been recently proposed as a possible grain constituent by Zhang et al (2009). Thus, depletion onto dust in DLAs probably cannot explain this difference.…”
Section: [S/mentioning
confidence: 94%
“…We show that MgS is a viable candidate to explain the 30 μm feature independent of the absorbing efficiencies of these grains at λ < 10 μm. Moreover, we show that if one assumes thermal contact between the dust species in the outflow, the mass problem in HD 56126 reported by Zhang et al (2009) does not occur in LL Peg. Finally, we discuss the formation of composite grains in AGB outflows.…”
Section: Introductionmentioning
confidence: 71%
“…In an analysis of this data set, Hony et al (2002) concluded that the shape of the 30 μm feature can be best reproduced when the grains are not perfect spheres. Zhang et al (2009) modeled the 30 μm feature in the proto-planetary nebula HD 56126 using pure MgS grains. Assuming the grains to be irradiated by unattenuated stellar light, their analysis needed the optical properties of MgS at wavelengths λ < 10 μm.…”
Section: Introductionmentioning
confidence: 99%